Effects of post-heat treatments on the microstructure and mechanical properties of Ti–6Al–4V alloy fabricated by selective laser melting - Yuantao Zhao; Yongkang Yue; Wenlong Deng; Jiansheng Li; Ming Chen; Shenqiang Liu; Wenge Li; Yanbo Liu; Vincent Ji (Journal of Materials Research and Technology)
In this study, post-heat treatments were applied to Ti–6Al–4V (TC4) alloy fabricated by selective laser melting (SLM) to investigate the effects of annealing temperature (750–950 °C in 50 °C intervals) on the alloy's microstructure, residual stress and mechanical properties. The initial microstructure of as-SLMed TC4 alloy was dominated by needle-like α′ martensite with a high density of dislocations and minor β phase, resulting in high strength (1190 MPa) but limited ductility (2.2% elongation). Annealing led to the transformation of α′ martensite into α phase, with the β phase content remaining relatively stable. Increasing the annealing temperature caused the acicular martensite to evolve into bundles of coarse α laths, forming a basket-weave microstructure. Annealing at 750 °C for 2 h reduced the yield strength to 1040 MPa and improved elongation to 8.3%. Interestingly, both the strength and ductility decreased with further increases in annealing temperature. This unusual phenomenon was rarely mentioned in current literature and was considered to be associated with the abnormal variations in the Schmid factor of (0001) [11-20] slip system and the reduction of mobile dislocations within the coarsened α martensite. Additionally, annealing combined with air cooling effectively alleviated residual tensile stresses in the SLM-formed TC4 alloy.